2018
DOI: 10.4314/sajas.v48i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Potential of white garlic powder (<i>Allium sativum</i> L.) to modify <i>in vitro</i> ruminal fermentation

Abstract: The current study aimed to evaluate the effect of increasing doses of garlic powder (GaP) on in vitro fermentation characteristics. Two successive 24-hour incubations were run, and gas production was measured at the end of each incubation period. Liquid samplings for each dose were reserved to determine ammonia nitrogen (NH 3 -N) and true organic matter degradability (TOMD). Partitioning factor (PF) was estimated as the ratio between TOMD and the gas produced at 24 hours of incubation. Microbial biomass (MBM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
3
10
2
Order By: Relevance
“…These results are in good agreement with similar observation that supplemental GAP had improved CP digestibility (Wanapat et al, 2008 a, b), DM and OM digestibility (Patra-Kamra et al, (2011) and Mirzaei et al, (2012). The results also reinforced by a recent study showed that dietary GAP supplementation increased (P < 0.05) in vitro digestibility of DM (Sahli et al, (2018). The significant improvement in nutrients digestibility noticed in the present study on lambs and reported by others (Zafarian and Manafi, 2013), may be referred as a result of GAP includes an oil containing organosulfur which could act as an antibacterial agent.…”
Section: Nutrients Digestibility and Nutritive Valuessupporting
confidence: 89%
See 2 more Smart Citations
“…These results are in good agreement with similar observation that supplemental GAP had improved CP digestibility (Wanapat et al, 2008 a, b), DM and OM digestibility (Patra-Kamra et al, (2011) and Mirzaei et al, (2012). The results also reinforced by a recent study showed that dietary GAP supplementation increased (P < 0.05) in vitro digestibility of DM (Sahli et al, (2018). The significant improvement in nutrients digestibility noticed in the present study on lambs and reported by others (Zafarian and Manafi, 2013), may be referred as a result of GAP includes an oil containing organosulfur which could act as an antibacterial agent.…”
Section: Nutrients Digestibility and Nutritive Valuessupporting
confidence: 89%
“…Similar effects of supplemental GAP on NH 3 -N were detected by Yang et al,. (2007), Kongmun et al, (2010) and Sahli et al, (2018). Ruminal NH3-N considered the most important nitrogen source for synthesis of microbial protein in the rumen (Wanapat and Pimpa, 1999).…”
Section: Nitrogen Balance and Rumen Liquor Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Rumen fermentation of ruminants would change after infection by GINs due to the complex interplay between GINs and host commensal flora [34]. Sahli et al (2018) did not find any changes in in vitro rumen fermentation by including garlic powder [14], while Busquet et al (2005a) revealed that garlic oil feeding decreased the molar proportion of acetate and increased the proportions of propionate and butyrate in an in vitro fermented system [35]. Our in vivo study found that dietary garlic powder supplementation increased total VFA content and the proportion of acetate, propionate, and isovalerate, but reduced the ratio of acetate to propionate.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, supplementing garlic powder, which contains all bioactive components and is prepared through simple steps, may be an alternative and practical strategy to deliver bioactive compounds to livestock. Furthermore, previous work conducted to examine the usefulness of garlic/garlic extract as a supplement in livestock production focused on growth performance [12], health [13], or in vitro rumen function [14]. For all we know, there is limited research investigating the supplementation of garlic powder or extract effect on sheep-infected GINs, which includes growth, digestion, rumen metabolism, and health status within one study.…”
Section: Introductionmentioning
confidence: 99%